Challenges Associated With Moving the United States Medical Licensing Examination (USMLE) Step 1 to After the Core Clerkships and How to Approach Them. (June 2019) - Pock, Arnyce; Daniel, Michelle; Santen, Sally A.; Swan-Sein, Aubrie; Fleming, Amy; Harnik, Vicky
Abstract : An increasing number of medical schools have moved away from traditional 2 + 2 curricular structures toward curricula that intentionally integrate basic, clinical, and health systems science, with the goal of graduating physicians who consistently apply their foundational knowledge to clinical practice to improve the care of patients and populations. These curricular reforms often include a shortened preclerkship phase with earlier introduction of learners into clinical environments. This has led schools to reconsider the optimal timing of United States Medical Licensing Examination Step 1. A number of schools have shifted the exam to the period immediately after core clerkships. Although this shift can provide pedagogical advantages, there are potential challenges that must be anticipated and proactively addressed. As more institutions consider making this change, key educational leaders from five schools that repositioned the Step 1 exam after core clerkships share strategies for mitigating some of the potential challenges associated with this approach. The authors describe six possible challenges: lack of readiness without consolidation of basic science knowledge prior to clerkships; risk that weaker students will not be identified and provided academic support early; clerkship or clinical shelf exam performance weaknesses; extension of Step 1 study time; an increase in student anxiety about residency specialty choices; and/or a reduced time frame to take and pass board exams. These potential challenges may be addressed using three main strategies: effective communication with all stakeholders; curricular design and assessments that facilitate integration of basic and clinical sciences; and proactive student coaching and advising.